THE IMPACT OF STUNTING MALNUTRITION OF ORODENTAL HEALTH IN CHILDREN: A SCOOPING REVIEW - I Gusti Ayu Ari Agung; Dewa Made Wedagama; I Gusti Ayu Agung Hartini; Ni Putu Widani Astuti; I Nyoman Panji Triadnya Palgunadi; Gusti Ayu Yohanna Lily; Ni Putu Idaryati; Ilma Yudistian (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Short children or commonly called stunting is a prevalent nutritional issue found among children globally. Indonesia has a notably high prevalence of stunting throughout the Southeast Asian region. Stunting malnutrition children will experience disturbances in the process of tooth growth, affecting the teeth during pre-eruption. Aim to provide an overview of the impact of stunting malnutrition on dental health in children. Materials and Methods: This study uses the PRISMA method, with the steps: (1) Question framework (literature study); (2) Search for articles in databases (on Scopus, PubMed, and Google Scholar), and journal databases with articles published from 2020 to 2022; (3) Selection of relevant research; (4) Data extraction; (5) Synthesis with narrative method. Results and Discussions: The study obtained 7 articles to be reviewed, proving that stunting malnutrition children experienced delayed tooth eruption in 3 articles; 4 articles analyzing the impact of stunting malnutrition on dental caries; and experiencing unhealthy dental health status in 1 article. Conclusion: The impact of stunting malnutrition children on orodental health is delayed tooth eruption, and severe dental caries.